ICCAD-2005. IEEE/ACM International Conference on Computer-Aided Design, 2005.
DOI: 10.1109/iccad.2005.1560075
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and compilation for data bandwidth improvement in configurable embedded processors

Abstract: Many commercially available embedded processors are capable of extending their base instruction set for a specific domain of applications. While steady progress has been made in the tools and methodologies of automatic instruction set extension for configurable processors, recent study has shown that the limited data bandwidth available in the core processor (e.g., the number of simultaneous accesses to the register file) becomes a serious performance bottleneck.In this paper we propose a new low-cost architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Though the previous works [4,5,12] improve the data bandwidth, they do not address the related problems of encoding multiple operands in a fixed-length instruction format and data hazards.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the previous works [4,5,12] improve the data bandwidth, they do not address the related problems of encoding multiple operands in a fixed-length instruction format and data hazards.…”
Section: Related Workmentioning
confidence: 99%
“…Cong et al [4,5] eliminate these explicit transfer of operands with the help of a shadow register file associated with the CFU. Shadow register file is similar to the internal register file of Nios-II in that they both provide input operands to the CFUs.…”
Section: Related Workmentioning
confidence: 99%
“…While steady progress has been made in the tools and methodologies of automatic instruction set extension for configurable processors, recent study has shown that the limited data bandwidth available in the core processor (e.g., the number of simultaneous accesses to the register file) becomes a serious performance bottleneck. [10] proposes a new low-cost architectural extension and associated compilation techniques to address the data bandwidth problem. [10] also present a novel simultaneous global shadow register binding with a hash function generation algorithm to take full advantage of the extension.…”
Section: Related Workmentioning
confidence: 99%
“…[10] proposes a new low-cost architectural extension and associated compilation techniques to address the data bandwidth problem. [10] also present a novel simultaneous global shadow register binding with a hash function generation algorithm to take full advantage of the extension. The application of this approach leads to a nearly-optimal performance speedup (within 2% of the ideal speedup).…”
Section: Related Workmentioning
confidence: 99%
“…Cong, Han and Zhiru Zhang (2005) [5] represents a very low cost architectural extension and a compilation technique responsible for data bandwidth problem. A novel parallel global register binding is also presented in [5] with the help of hash function algorithm. This leads to a nearly optimal performance speedup of 2% of ideal speedup.…”
Section: Related Workmentioning
confidence: 99%